Clinical findings from 104 cases of calving paralysis in dairy cows from Gippsland, Australia. Issue 4 (4th July 2019) - Poulton, PJ; Fisher, AD; Mansell, PD; Pyman, MF
ABSTRACT: Case History: Dairy cows recumbent following calving on farms in South Gippsland, Australia were examined during two 3-month seasonal calving periods in 2011 and 2012 as part of a larger study of 218 recumbent cows. A cohort of 104 cows diagnosed with calving paralysis following dystocia was derived from the larger group, which were examined with 3 days of becoming recumbent. A thorough medical and musculoskeletal clinical examination was performed on each cow including flexor-withdrawal and patellar reflex tests, and postural assessment in the lifted position, unless the facilities were not available. Cows were diagnosed with one or more neurological syndromes: sciatic, tibial paresis, obturator or femoral, based on clinical findings consistent with damage to these peripheral nerves or their nerve roots. Clinical Findings: Evidence of sciatic syndrome was found in 100/104 (96.2%) cows and 146/172 (84.9%) affected hind limbs either as the sole neuropathy or in combination with tibial paresis, obturator or femoral syndromes. Pelvic damage was also present in 3/104 (2.8%) cows. Obturator syndrome was diagnosed in 30/104 (29%) cows and 45/172 (26.2%) affected hind limbs but not apparently as the sole reason for the recumbency. Femoral syndrome occurred in 16/104 (15.4%) cows and 21/172 (12.2%) affected hind limbs and was the only syndrome recorded in one cow. Clinical Relevance: Sciatic syndrome was the most common neurological syndrome observed in cows with calving paralysis. The other major nerves arising from the lumbo-sacral plexus were also affected and the various syndromes associated with damage to these nerves or their ventral nerve roots occurred in many combinations. Calving paralysis should be thought of as a paresis or paralysis resulting from damage to the ventral nerve roots of the lumbo-sacral plexus as any of the nerves originating from this plexus can be damaged during dystocia either individually or in combination with other nerves from the plexus.